#### Answer

(13)(7)

#### Work Step by Step

Given the number 91 we find two numbers that are perfect squares that add to give 91. We get +100 and -9
100 - 9
*** Take the square root of 100 which is 10. Becuase 10 × 10 = 100
*** Take the square root of 9 which is 3. Becuase 3 × 3 = 9
We rewrite it as the squares.
$10^{2}$ - $3^{2}$
We use the formula for the difference of squares to apply to this question.
The difference of squares formula is:
$(a-b) (a+b) = a^{2} - b^{2}$
In the given formula let 10 represents a and 3 represents b.
$10^{2}$ - $3^{2}$ = (10+3)(10-3)
= (10+3)(10-3)
= (13)(7)